(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores effective methods for fostering a sense of national pride in students through the study of the works of Imam Al-Bukhari. It emphasizes the importance of integrating historical, cultural, and religious values in education to develop patriotic feelings and moral awareness among young learners. Practical strategies and pedagogical approaches are discussed to enhance students’ understanding of their national heritage and identity.